1998
DOI: 10.1021/cm980130v
|View full text |Cite
|
Sign up to set email alerts
|

Order−Disorder Phenomena in New LaBaMn2O6-x CMR Perovskites. Crystal and Magnetic Structure

Abstract: Three new perovskites in the LaBaMn 2 O 6-x family have been synthesized by controlling the oxygen pressure, during both synthesis and postannealing. Structural determination from powder neutron diffraction (PND) data shows that one form of LaBaMn 2 O 6 is cubic (a ) 3.906 Å), with a disordered distribution of La 3+ and Ba 2+ cations, whereas a second form of LaBaMn 2 O 6 is tetragonal (a ) 3.916 Å; c ) 7.805 Å), with an alternate stacking of lanthanum and barium layers along c. The same La/Ba cation order is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
183
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(200 citation statements)
references
References 18 publications
17
183
0
Order By: Relevance
“…3). Surprisingly, the Curie points are much lower than that of La 0.5 Ba 0.5 MnO 3 (T C = 340 K) [14]. The relatively low magnetic moment may be attributed to a canted magnetic state or to a mixture of two magnetic phases.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…3). Surprisingly, the Curie points are much lower than that of La 0.5 Ba 0.5 MnO 3 (T C = 340 K) [14]. The relatively low magnetic moment may be attributed to a canted magnetic state or to a mixture of two magnetic phases.…”
Section: Resultsmentioning
confidence: 80%
“…However, it is well known that they do not exhibit antiferromagnet-ferromagnet and charge order-disorder transitions. It was found that La 0.5 Ba 0.5 MnO 3 is a ferromagnet with T C ≈ 340 K [14]. The Pr 0.5 Ba 0.5 MnO 3 and Nd 0.5 Ba 0.5 MnO 3 have Curie points of 125 K [15] and 120 K [16], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Millange et al demonstrated that it is possible to synthesize mixed valence compounds A 0.5 A ′ 0.5 MnO 3 in which the A 3+ and A ′2+ cations order periodically in lattice structure. 23 These special compounds, which are called the A-site ordered manganites, exhibit distinct properties from the materials with random configuration of A-site cations. We can compare the 'clean' systems (A-site ordered) and the 'dirty' systems (A-site disordered) both of which have the same chemical formula.…”
Section: A-site Order/disorder Materialsmentioning
confidence: 99%
“…For BaYMn 2 O 5+δ , substitutions of the lanthanoid (Ln) series at the yttrium site were extensively investigated, although the interests in previous works were mainly devoted to the electronic properties. [14][15][16][17][18] Recent reports by Swierczek and coworkers evidenced [19][20][21] that…”
Section: Introductionmentioning
confidence: 97%